2011
DOI: 10.1038/bcj.2011.2
|View full text |Cite
|
Sign up to set email alerts
|

Specific cellular signal-transduction responses to in vivo combination therapy with ATRA, valproic acid and theophylline in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) frequently comprises mutations in genes that cause perturbation in intracellular signaling pathways, thereby altering normal responses to growth factors and cytokines. Such oncogenic cellular signal transduction may be therapeutic if targeted directly or through epigenetic regulation. We treated 24 selected elderly AML patients with all-trans retinoic acid for 2 days before adding theophylline and the histone deacetylase inhibitor valproic acid (ClinicalTrials.gov NCT00175812; Eudr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“… 32 , 63 In this regard, it is noteworthy that a proteomics study in AML identified a signature of four phosphorylated proteins that act as predictors for response to the FLT3-targeted tyrosine kinase inhibitor, quizartinib. 64 Proteomics of AML is still in its infancy, 65 but may allow delineation of defined signal transduction and tumor suppressor pathways in single cells or cell extract assay: 66 , 67 sample formats that may be relevant for future clinical trials of Plk1-targeting therapy. Relevant markers might be also identified based on comprehensive genomic, epigenomic and transcriptomic analyses.…”
Section: Potential Biomarkers Of Volasertib Sensitivitymentioning
confidence: 99%
“… 32 , 63 In this regard, it is noteworthy that a proteomics study in AML identified a signature of four phosphorylated proteins that act as predictors for response to the FLT3-targeted tyrosine kinase inhibitor, quizartinib. 64 Proteomics of AML is still in its infancy, 65 but may allow delineation of defined signal transduction and tumor suppressor pathways in single cells or cell extract assay: 66 , 67 sample formats that may be relevant for future clinical trials of Plk1-targeting therapy. Relevant markers might be also identified based on comprehensive genomic, epigenomic and transcriptomic analyses.…”
Section: Potential Biomarkers Of Volasertib Sensitivitymentioning
confidence: 99%
“…The algorithm used for the digital analysis was developed using MATLAB (MathWorks, Natick, Massachusetts). The patients were randomly selected from a previously characterized cohort (n = 97) where the ultrasound findings correlated with objective findings such as reduced saliva secretion, minor salivary gland inflammation and elevated autoantibody titers, as well as sicca symptoms of the mouth (3). Results: Preliminary findings show an excellent correlation between the scores obtained with the simplified grading system (0-3) and the automated digital evaluation of local variability in grayscale values (P < 0.05, r = 0.816, n = 26).…”
Section: Methodsmentioning
confidence: 99%
“…34.5% pts (29/84): 7 pts with systemic manifestations, 15 with MALT lymphoma, seven with hypergammaglobulinemia) were under RTX maintenance therapy for median 48 (33-60) months. Median RTX cumulative dose of during it was 2.5 gr (2)(3)(4). Results: At month three after RTX induction therapy, there was significant improvement in pSS (see Table 1).…”
Section: Il17mentioning
confidence: 99%
See 2 more Smart Citations